(untitled) (Profetik: Jurnal Komunikasi, 2022)
Cinemas or movie theaters are one of the industries that can hold its own amidst digital disruption. As a means of distribution and exhibition of conventional films, cinemas have the ability to adapt themselves to various digital innovations; starting from the audio-visual projection device, ticketing, payment system to 3D technology. The existence and survival of a cinema rely on two factors, namely film distribution and moviegoer factors, the COVID-19 pandemic has shifted these two factors. If previously movie distribution and moviegoing occurred conventionally, the two activities have shifted considerably to online distribution/streaming. This study analyzed the paradigm shift in film distribution and moviegoing during and after the pandemic using a “three-stage model of theory building” as an analytical tool which is part of the descriptive-qualitative methodology. The results showed that the COVID-19 pandemic is an anomaly that is shifting the paradigm in conventional film distribution as evidenced by the fact that it is not new media that pose a threat to the existence of cinemas, but the insubstantial social functions and cinema activities during the pandemic. There are five factors why cinemas will continue to develop as a film distribution and exhibition medium post COVID-19: cinema adaptation, big screen sensation, entertainment and social values, historical values, and economic factors.